Durability of Very-High-Strength Concrete with Supplementary Cementitious Materials for Marine Environments - Lim, Tze Yang Darren (2016)
This paper summarizes the findings from a research program to investigate the effects of different amounts of supplementary cementitious materials on improving the concrete mechanical properties and on increasing the resistance to chloride penetration for applications in marine environments. Twelve concrete mixtures with different quantities and compositions of supplementary materials were tested. The durability properties with respect to chloride penetration, such as electrical resistivity and chloride diffusivity, were correlated with each other. A good correlation between them was obtained, as validated by the test results. The inclusion of supplementary cementitious materials in sufficient amounts, such as ground-granulated blast-furnace slag and silica fume, proved to be highly effective in improving the durability properties of the concrete. In addition, an increase in the fineness of ground-granulated blast-furnace slag would benefit early-age strength development of the concrete. The inclusion of supplementary cementitious materials in sufficient amounts is essential to obtaining a concrete mixture with good mechanical properties and high resistance against chloride ingress.